2017
DOI: 10.1177/0361684317742638
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of Myths About Intimate Partner Violence Against Women (AMIVAW) Scale

Abstract: The measures available for assessing the acceptance of myths about intimate partner violence against women (AMIVAW) are characterized either by a lack of sufficient psychometric support or by being based on unclear theoretical propositions. In this article, we present a 15-item self-report scale: the Acceptance of Myths About Intimate Partner Violence Against Women (AMIVAW) Scale. We examined the reliability and validity of the scores of the Spanish and English versions of this scale across six different sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 67 publications
5
46
0
24
Order By: Relevance
“…For example, victim-blaming attitudes, traditional gender role beliefs, hostile sexism, and acceptability of IPVAW have been linked to a lesser willingness to intervene in cases of IPVAW (i.e., a preference for calling law enforcement and a lack of preference for nonintervention) [ 22 , 27 ]. Moreover, the endorsement of myths or misconception beliefs about rape or IPVAW promotes a greater victim blame and exoneration of perpetrator, withholding the sense of personal responsibility to intervene [ 20 , 30 , 31 ]. Additionally, Beeble et al [ 29 ] found, using a representative U.S. sample, IPVAW victims were more likely to be helped by those who had a consciousness about the high prevalence of IPVAW in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, victim-blaming attitudes, traditional gender role beliefs, hostile sexism, and acceptability of IPVAW have been linked to a lesser willingness to intervene in cases of IPVAW (i.e., a preference for calling law enforcement and a lack of preference for nonintervention) [ 22 , 27 ]. Moreover, the endorsement of myths or misconception beliefs about rape or IPVAW promotes a greater victim blame and exoneration of perpetrator, withholding the sense of personal responsibility to intervene [ 20 , 30 , 31 ]. Additionally, Beeble et al [ 29 ] found, using a representative U.S. sample, IPVAW victims were more likely to be helped by those who had a consciousness about the high prevalence of IPVAW in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…Situadas en nuestro ámbito laboral, el debate en estos términos es una parte fundamental para encaminar la mejora de nuestra formación, si pretendemos interpretar de modo profesional a migrantes con estas experiencias, como también lo es el análisis de algunos mitos y prejuicios asentados y compartidos ampliamente en el contexto español. A continuación, comentamos brevemente varios de ellos, en lo que sería una propuesta de algo que, además de ser discutido a nivel teórico-práctico en las formaciones de los y las intérpretes que trabajen en estos contextos, convendría investigar en la práctica aplicada a nuestro ámbito -adaptando, por ejemplo, el modelo de evaluación de mitos sobre la violencia de género propuesto por Megías et al (2017)-. De este modo, se podrían extraer datos concretos con los que poder reivindicar, de forma más efectiva, la necesidad inminente de una perspectiva de género y decolonial en la interpretación.…”
Section: Towards Transnational Feminist Translation Studiesunclassified
“…La violencia de género constituye un problema de salud pública y tiene implicaciones tanto en el ámbito privado como en el ámbito público (Campbell, 2001;Gómez Hermoso et al, 2012;Megías et al, 2017). Lejos de tratarse de una experiencia individual (Abril Martí, 2015; Toledano Buendía y Del Pozo Triviño, 2015), es un hecho cultural fundamentado en una estructura heteropatriarcal que históricamente reproduce la subordinación de las mujeres (Pérez Freire y Casado Neira, 2015), de las personas trans y de otras identidades disidentes con respecto al hombre heterosexual cisgénero.…”
Section: Mito O Prejuicio Ejemplos Consideracionesunclassified
See 2 more Smart Citations